1981
DOI: 10.1152/ajpheart.1981.240.4.h511
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cerebral arteriolar abnormalities after acute hypertension

Abstract: Acute severe hypertension induced by intravenous norepinephrine or angiotensin in anesthetized cats equipped with a cranial window caused prolonged arteriolar vasodilation associated with reduced responsiveness to arterial hypercapnia or hypocapnia and passive response to changes in arterial blood pressure. Scanning and transmission electron microscopy of such pial arterioles showed discrete destructive endothelial lesions the density of which correlated with the degree of vasodilation. Abnormalities of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 0 publications
3
87
0
Order By: Relevance
“…However, oxygen-derived free radicals have been suggested to participate in the pathogenesis of hypertensive vascular disease by increasing vascular permeability and contractility as well as by inducing cellular injury, the interpretation of which is based on the inhibitory effects of free radical scavengers. [11][12][13]40 The biological effects seen with oxygen-derived free radicals noted above also occur with ChOx.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, oxygen-derived free radicals have been suggested to participate in the pathogenesis of hypertensive vascular disease by increasing vascular permeability and contractility as well as by inducing cellular injury, the interpretation of which is based on the inhibitory effects of free radical scavengers. [11][12][13]40 The biological effects seen with oxygen-derived free radicals noted above also occur with ChOx.…”
Section: Discussionmentioning
confidence: 94%
“…Although the pathogenesis of free radicals in hypertension is incompletely understood, many sources are possible, including free radical generation by polymorphonuclear leukocytes and enhanced production of radical species and oxidants by endothelium and smooth muscle cells. 5,11,41 Cellular oxidative modification of cholesterol is thought to involve endothelial-and macrophagederived reactive oxygen species. 36,42,43 Hypertension, which increases arterial wall thickness and oxygen diffusion, produces medial hypoxia and steep oxygen tension gradients within the wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En-dothelial damage ranged from discrete endothelial lesions in pial arterioles 4 and intestinal arterioles 5 to disruption of cellular junctions and increases in vascular permeability in mesenteric vessels 6 and focal areas of endothelial denudation and platelet adherence in mesenteric arterioles. 7 In the cerebral circulation, acute hypertension not only damaged pial artery endothelium but also abolished dilation to acetylcholine and resulted in constriction of pial arteries to acetylcholine.…”
Section: -3mentioning
confidence: 99%
“…These abnormalities are known to be caused by cyclooxygenase-derived free radicals since they can be prevented by cyclooxygenase inhibitors and oxygen radical scavengers. 6 ' 7 Additionally, we have very recently shown that the increases in cerebrovascular permeability and brain water content caused by norepinephrine-induced hypertension can be prevented by the systemic administration of superoxide dismutase. 8 In recent years, investigators have become interested in the endothelium and its generation of relaxing factors.…”
mentioning
confidence: 99%